Report on Faculty Activities Policy, November 20, 2014 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2014)
Valdosta State University. Faculty Senate, Report on Faculty Activities Policy, November 20, 2014. Document discusses Valdosta State University and Georgia Board of Regents policies regarding faculty political activity, referencing Mark George and the Mary Turner Project.
1 electronic document. faculty-senate_grove-request.pdf, 81 pages.
Keywords: Faculty Senate (Valdosta State University); Electronic records; Corporation reports; Universities and colleges--Faculty--Political activity; College teachers -- Political activity